Chemical Components from the Light Petroleum Soluble Fraction of Uvaria cordata (Dunal) Alston - Mahmood, Kamaliah; Mohd Ali, Hapipah; Yusof, Rohana; Hadi, A. Hamid (Universiti Putra Malaysia Press, 1995)
Chromatographic separation of the light petroleum extract from the stem bark of Uvaria cordata (Dunal) Alston led to the isolation of the triterpenoids glutinol and taraxerol in addition to the cyclohexene derivatives, pipoxide and its chlorohydrin. A small amount of benzyl benzoate was also isolated.